Livestock under threat: Managing the future of native West African ruminant livestock - International Livestock Research Institute (2011)
There is more livestock diversity in Africa than on any other continent. Some indigenous breeds of cattle, goats and sheep are disease resistant, and others can withstand feed and water shortages. But most are less productive than some imported breeds and so do not meet farmers' needs. Millions of poor livestock keepers are importing animals, or cross breeding with imported breeds to get more productive livestock. But imported breeds need expensive care because they are much less hardy, and animal deaths are increasing. There is a danger that many of Africa's indigenous hardy livestock breeds will disappear, just as climate changes and population growth is making their hardy traits increasingly important for food security across the region. This film tells the story of a unique research and development project that aims to increase understanding of trypanotolerant livestock and the people who rear them along with what is needed to improve markets and processing for livestock products. This information will then be combined with better feeding and breeding schemes, farmer training and policy changes to make indigenous animals more profitable for poor farmers, so that their future use becomes sustainable.